2021
DOI: 10.1073/pnas.2117017118
|View full text |Cite
|
Sign up to set email alerts
|

Adult mouse and human organoids derived from thyroid follicular cells and modeling of Graves’ hyperthyroidism

Abstract: The thyroid maintains systemic homeostasis by regulating serum thyroid hormone concentrations. Here we report the establishment of three-dimensional (3D) organoids from adult thyroid tissue representing murine and human thyroid follicular cells (TFCs). The TFC organoids (TFCOs) harbor the complete machinery of hormone production as visualized by the presence of colloid in the lumen and by the presence of essential transporters and enzymes in the polarized epithelial cells that surround a central lumen. Both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 57 publications
1
27
0
Order By: Relevance
“…[ 11 ] Consistently, the dependence of adult TFC cells on the cAMP pathway has been reported by the latest study on adult mouse and human thyroid organoids. [ 30 ] However, when cAMP initiated in fetal thyroid and when subsequent cascade events occur in the narrow time window from thyroid organogenesis to functional maturation still remain elusive. Our study indicates the significance of cAMP activation during fetal thyroid maturation and demonstrates heterogeneity of fetal thyrocytes in cAMP signal response.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] Consistently, the dependence of adult TFC cells on the cAMP pathway has been reported by the latest study on adult mouse and human thyroid organoids. [ 30 ] However, when cAMP initiated in fetal thyroid and when subsequent cascade events occur in the narrow time window from thyroid organogenesis to functional maturation still remain elusive. Our study indicates the significance of cAMP activation during fetal thyroid maturation and demonstrates heterogeneity of fetal thyrocytes in cAMP signal response.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with results from a recent study by van der Vaart et al . in thyroid organoids who could not find evidence for the existence of unique thyroid stem cells (26). They described that many solid tissues do not rely on a professional stem cell for their maintenance and repair, but rather temporarily recruit differentiated cells into a transient progenitor pool (26), suggesting that this phenomenon is also applicable to the thyroid or in this case even parathyroid gland.…”
Section: Discussionmentioning
confidence: 99%
“…When comparing immunolabeling of parathyroid tissue with parathyroid organoids, similarities were seen in the expression pattern of GCM2, CHGA, PTH and CaSR (Figure 4). To study the presence of stem cell markers in human PTOs, we analyzed the most proposed stem cell markers as listed by van der Vaart et al (26), using bulk RNA-sequencing. No upregulation was observed in the putative stem cell markers MKI67, ATXN1, FUT4, REOX1, HHEX, NGFR, TTF2 and SOX2, when comparing PTOs and dPTOs to tissue (Supplemental Figure 6).…”
Section: Characterization Of Parathyroid Organoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Graves’ disease (GD) is an autoimmune disease with the overproduction of thyroid-stimulating hormones (TSH) induced by the activation of thyrotropin-receptor antibodies (TRAb) ( 1 ). It is the most common cause of hyperthyroidism, which has significant adverse effects on many organ systems, such as cardiovascular, metabolism, growth, and gastrointestinal ( 2 ). Epidemiological studies showed that the incidence of Graves’ hyperthyroidism in the United States is around 20–40 cases per 100,000 individuals per year ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%